Development of a multimedia enhanced web prototype for technical learning instrument - Ismail, Izwan (2003)
Inconveniences in apparatus preparation, increased number of students and time constraints had caused the development of alternative learning instrument. Thus, a research on development and evaluation of multimedia enhanced web site as a learning instrument for metallogaphy subject was conducted. A website namely Visual Metallography (VM) was designed and enhanced with multimedia as the information transmission medium. Video clips were used to elaborate the specimen preparation process in laboratory whereas; animation was included to enhance the interactive circumstance. VMwas evaluated using questionnaire with a group of respondent. Reliability level of instrument used was determined through a pilot test. Cronbach's alpha for section 2, 3 and 4 were 0.942, 0.839 and 0.813 respectively. The research sample comprised 50 engineering students of KUiTTHO enrolling for Metallography subject. Research findings were analysed descriptively using SPSS 11.0 software. Referring to the analysed data, 55 items were highly rated except for item 23, which rated at medium level. In conclusion, the interface (GUI) design, multimedia provided and learning style presented in VMweb were fulfilling the users' needs. VMis indeed suitable as a multimedia-enhanced web based learning instrument purposely for lecturers and students.